A high-resolution sedimentology and age determination of core PS2185 from the central Arctic Ocean, supplementary data to: Spielhagen, Robert F; Bonani, Georges; Eisenhauer, Anton; Frank, Martin; Frederichs, Thomas; Kassens, Heidemarie; Kubik, Peter W; Mangini, Augusto; Nørgaard-Pedersen, Niels; Nowaczyk, Norbert R; Schäper, Stefan; Stein, Ruediger; Thiede, Jörn; Tiedemann, Ralf; Wahsner, Monika (1997): Arctic Ocean evidence for late Quaternary initiation of northern Eurasian ice sheets. Geology, 25(9), 783-786 - Spielhagen, Robert F.; Bonani, Georges; Eisenhauer, Anton (PANGAEA - Data Publisher for Earth & Environmental Science, 1997)
A high-resolution multiparameter stratigraphy allows the identification of late Quaternary glacial and interglacial cycles in a central Arctic Ocean sediment core. Distinct sandy layers in the upper part of the otherwise fine-grained sediment core from the Lomonosov Ridge (lat 87.5?N) correlate to four major glacials since ca. 0.7 Ma. The composition of these ice-rafted terrigenous sediments points to a glaciated northern Siberia as the main source. In contrast, lithic carbonates derived from North America are also present in older sediments and indicate a northern North American glaciation since at least 2.8 Ma. We conclude that large-scale northern Siberian glaciation began much later than other Northern Hemisphere ice sheets.
This dataset is supplement to doi:10.1130/0091-7613(1997)025<0783:AOEFLQ>2.3.CO;2
Keywords: Datensammlung